PENGEMBANGAN POP-UP BOOK DITO AUMENTED REALITY SEBAGAI MEDIA MEMBACA PERMULAAN BERNUANSA BUDAYA LOKAL UNTUK SISWA KELAS 1 SD - Amanda Berlia Bersky; Kurnia Shandi; Melani Adila Putri; Nurul Azmi; Tiok Wijanarko (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to overcome the low reading ability of first-grade elementary school students by developing learning media in the form of pop-up books based on augmented reality (AR) that focus on local culture. This study uses the Research and Development (R&D) method with five stages, namely analysis, design, development, implementation, and evaluation. The results of the study showed that the media developed had high validity, with an average of 91%, considered very valid by experts. Practicality tests by teachers and students showed an average of 96%, which was considered very practical in its use. The effectiveness of this medium was tested through various statistical tests, including normality tests, which showed that the data were normally distributed in both groups, the experimental and control groups. The paired sample t-test showed a significant difference between student learning outcomes in the pre-test and post-test in the experimental class using AR-based pop-up books, with a Sig. (2-tailed) value of 0.000 <0.005. The same test in the control class also showed a significant difference. In addition, the independent sample t-test showed that the average post-test score of students in the experimental class was higher (78.15) compared to the control class (68.20). Overall, this study proves that the use of AR-based pop-up book media is effective in improving students' beginner reading skills and has a high level of validity and practicality. This shows that the use of pop-up book media has been proven effective in helping students improve their beginner reading skills.